Effects of coenzyme Q10 on endothelial and cardiac function in patients undergoing haemodialysis: study protocol for a pilot randomised controlled trial - Yongxing Xu; Enhong Han; Jianjun Gao; Xinlou Li; Xiaowen Zuo; Huaping Jia; Fugui Liang; Lei Xie (BMJ Open, 2020)
Introduction Endothelial and cardiac dysfunction are highly prevalent and are associated with cardiovascular morbidity and mortality among patients undergoing dialysis. For patients undergoing dialysis, no study has explored the effect of supplementation of coenzyme Q10 (CoQ10) on endothelial function. To our best of knowledge, only two small sample studies focused on the efficacy of supplementation of CoQ10 on cardiac function. However, the effect of CoQ10 supplementation on cardiac function remains uncertain in patients who undergo haemodialysis. The aim of this study is to explore whether CoQ10 supplementation can improve endothelial and cardiac function in patients undergoing haemodialysis.Methods and analysis This is a pilot randomised controlled study. Eligible patients undergoing haemodialysis in our haemodialysis centre will be randomly allocated to the CoQ10 and control groups. The follow-up time is 12 months. The primary outcome is to assess the change of brachial artery endothelial-dependent flow-mediated dilation, left ventricular systolic function, diastolic function and Myocardial Performance Index at 12 months from baseline. Secondary outcomes are death or hospitalisation due to cardiovascular events, all-cause mortality, change of CoQ10 concentration, the ratio of ubiquinol to ubiquinone, the change of oxidative stress markers (including malondialdehyde and 8-hydroxy-deoxyguanosine) and Left Ventricular Mass Index.Ethics and dissemination Risks associated with CoQ10 are minor, even at doses as high as 1800 mg according to previous studies. The trial has received ethics approval from the Medical Ethics Committee for Clinical Trials of Drugs, the 306th Hospital of Chinese PLA. The results of the study are expected to be published in a peer-reviewed journal and presented at academic conferences.Trial registration number ChiCTR1900022258.